Wisdom's root revealed : Ben Sira and the election of Israel - Goering, Greg Schmidt. (Supplements to the Journal for the Study of Judaism, 2009)
This monograph interprets the theme of election in the book of Sirach. Previous scholarship has often understood Ben Sira's worldview to be dualistic, and has approached the sage's correlation of Wisdom and Torah as either a nationalization of Wisdom or a universalization of Torah. By probing Ben Sira's ideas about election, this book suggests that Ben Sira does not collapse the traditional sapiential dichotomy wisdom/folly into a dualistic worldview, and that his understanding of the relation between Wisdom and Torah proves to be far more subtle than previous interpretations have allowed. The study demonstrates that the concept of election enables a profitable discussion of the relation of Wisdom and Torah in the thought of this pivotal Second Temple sage.